Peranan Pemerintah dalam Pembinaan dan Pemberdayaan Pedagang Kuliner di Pajak USU (Pajus), Kecamatan Medan Baru - Ompusunggu, Vina Maria; Munthe, Rikawati Ginting; Sitorus, Hans Cristian Pandapotan; Silitonga, Aldi Ferdiansyah (Universitas Quality, 2024)
One of the main tasks of the local government and its apparatus is community empowerment. Thus, government officials in the region are always required to take a big role in empowering the people in their area. USU Tax (Pajus) is a form of people's economy that contributes greatly to the pillars of the economy in Medan City. The purpose of this research is to find out the role of the government in empowering USU tax to improve the welfare of the community in USU Tax, Medan Baru District. The research method used is qualitative research. In this case the author focuses on research that is seen from a good government (good governance) including: Participaton, Transparency, Respowiveness, Consensus of orientation and Accountability. This research was conducted at USU Tax, Medan Baru Subdistrict. In this case the government must prioritize the interests of the wider community, when viewed from the empowerment of the USU Tax in Medan Baru Subdistrict to improve the welfare of the existing community, the government must certainly develop this market, because the economic activities of the community are in this tax, if the government does not develop this tax, it means that the government does not prioritize the interests of the people who depend on living in this tax. USU Tax is a big responsibility for the government to be developed, because USU Tax is now competing with modern markets. Of course, the development of this traditional market requires a clear and precise strategy from the government itself to be able to answer every problem that exists in the development of traditional markets. The targeted output of this research is proposed in a SINTA 3 accredited journal, namely the Journal of Business Economics at the State University of Malang.